Role of high sensitive c-reactive protein and serum uric acid in coronary artery diseases: a case control study - Takkalaki, Nandini; Muchchandi, Raja Shekhar; N., Krishnamurthy (International Journal of Research in Medical Sciences, 2021)
Background: Coronary artery diseases (CAD) are considered to be the major public health concerns throughout the world, including India. Despite significant improvement in the diagnosis, treatment and prevention, CAD remains the most common, acute, and chronic illness, which is the leading cause of mortality and morbidity in the world. Methods: To estimate the serum uric acid and hs-CRP levels in coronary artery disease cases with diabetes mellitus and hypertension and compare with the healthy individuals. Results: The mean serum uric acid levels were raised in cases (6.1±1.54 mg/dl) compared to the controls (5.16±1.007 mg/dl) which was significant statistically (p<0.008). The mean hs-CRP levels were raised in cases (7.1±8.122 mg/dl) compared to the controls (0.185±0.254 mg/dl) which was highly significant statistically. Conclusions: Measurement of the levels of hs-CRP and serum uric acid in CAD might help in identifying the patient at increased risk of mortality.